2016
DOI: 10.1007/s13197-016-2404-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents and stability of betalains in fruit extracts of Malabar spinach (Basella rubra L.)

Abstract: This study aimed to assess the nutrient composition, minerals, and stability of betalains pigment from fruit extracts of . The proximate composition included total carbohydrates (1.64 g), protein (51 mg), total lipid (1.38%), moisture (81.76%), niacin (0.5 mg), ascorbic acid (89.33 mg), and total tocopherols (1.27 mg) in 100 g fresh deseeded fruit. Total dietary fibre of 32.52 g and soluble dietary fibre of 12.34 g in 100 g dry deseeded fruits. Fatty acid composition of dry deseeded fruits comprised 57.52% SFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
6
14
0
Order By: Relevance
“…The results are shown in Table II. Our results are in agreement with earlier findings which were reported by Ozela et al 6 , and Kumar et al 15 for B.rubra betalains and Reshmi et al 7 for Basella alba and relationships between these effects and the decomposition of the pigments has always been observed, in the present study also. Acids Different acids were selected to determine their influence on the colour stability under three different storage conditions.…”
Section: Preparation Of Pigment Solutionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results are shown in Table II. Our results are in agreement with earlier findings which were reported by Ozela et al 6 , and Kumar et al 15 for B.rubra betalains and Reshmi et al 7 for Basella alba and relationships between these effects and the decomposition of the pigments has always been observed, in the present study also. Acids Different acids were selected to determine their influence on the colour stability under three different storage conditions.…”
Section: Preparation Of Pigment Solutionsupporting
confidence: 94%
“…But, in presence of sodium benzoate 73% colour was retained in cold under dark condition. Similar findings were reported by Kumar et al 15 for aqueous extract of Basella rubra fruit in salt sodium chloride. Amino acids Two amino acids glutamic acid (monosodium glutamate) and aspartic acid were tested for their influence on betalain colour ( Figure II).…”
Section: Preparation Of Pigment Solutionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, these plant organs are used to prepare traditional beverages in the northern highlands of Puebla, Mexico. The endogenous levels of betanin in P. thyrsiflora were similar to those reported for Phytolacca americana, beetroot cultivars and the Malabar spinach [18,19]. Thus, the berries of P. thyrsiflora can be considered as a potential source to obtain betanin.…”
Section: Discussionsupporting
confidence: 81%
“…B. alba leaves are used in Ayurveda system of medicine as soothing agents, laxative, demulcent, astringent and the cooked roots are used in the treatment of diarrhoea (Kumar et al 2013). The tender stem of both the species contains gelatinous or mucilaginous substances (Kumar et al 2016). In-vitro assays, preclinical and clinical studies have shown that Basella exhibits antibacterial, anti-hyperglycemic, anti-inflammatory, cytotoxic and anti-proliferative activity (Priya et al 2015;Kumar et al 2015a, b, c;Kilari et al 2016).…”
Section: Introductionmentioning
confidence: 99%